Fashion and Beauty Center in Semarang City with an Organic Modern Architecture Approach - Setya Putri Agustina; Ari Rahadini; Teguh Prihanto; Isna Pratiwi (Universitas Negeri Semarang, 2024)
As the economy in Indonesia grows, the lifestyle of its people is dynamically changing. There is an increasing interest in fashion and beauty among the population, supported by the tendency of urban Indonesians to follow evolving fashion trends. Clothing (fashion) and beauty are crucial factors in personal appearance, thus creating a demand for facilities that cater to these needs within a single area. Semarang City is part of the mega-urban area known as Kedungsepur (Kendal, Demak, Ungaran, Salatiga, Semarang, and Purwodadi), which is a hub of urban development in Central Java. However, the growth of fashion and beauty in Semarang is uneven, despite the promising potential of the fashion and beauty industries to support local and regional economic growth. Therefore, there is a need for planning a facility that encompasses not only commercial aspects but also educational aspects within one area. The planning of a Fashion and Beauty Center aims to provide facilities to the community of Semarang City to support various activities such as shopping, salons, beauty treatments, fashion training, treatment training, makeup training, art galleries, and fashion shows. The application of a modern organic architectural approach in planning the Fashion and Beauty Center embodies the characteristics of fashion and beauty that are always evolving to be free-spirited, simple, functional, and elegant from year to year, while maintaining a balance with the surrounding environment.